2022
DOI: 10.3389/fchem.2022.868240
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome P450 OxyA from the Kistamicin Biosynthesis Cyclization Cascade is Highly Sensitive to Oxidative Damage

Abstract: Cytochrome P450 enzymes (P450s) are a superfamily of monooxygenases that utilize a cysteine thiolate–ligated heme moiety to perform a wide range of demanding oxidative transformations. Given the oxidative power of the active intermediate formed within P450s during their active cycle, it is remarkable that these enzymes can avoid auto-oxidation and retain the axial cysteine ligand in the deprotonated—and thus highly acidic—thiolate form. While little is known about the process of heme incorporation during P450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The acceptance of such amino acids in GPA biosynthesis could be beneficial in selective modification with further payloads [24] . However, modifying the C terminus of the linear GPA precursor peptide has been associated with a loss P450 activity, particularly with the second enzyme (OxyA) in the P450 cyclisation cascade that forms the D‐ O ‐E ring, [22] which has also been shown to be less stable than OxyB in certain cases [25] . In contrast to modification of the C terminus, modifications at the peptide N terminus appear to be more widely tolerated since it has been shown that the incorporation of aromatic residues such as those found in teicoplanin [26] or positively charged residues can be tolerated [18] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of such amino acids in GPA biosynthesis could be beneficial in selective modification with further payloads [24] . However, modifying the C terminus of the linear GPA precursor peptide has been associated with a loss P450 activity, particularly with the second enzyme (OxyA) in the P450 cyclisation cascade that forms the D‐ O ‐E ring, [22] which has also been shown to be less stable than OxyB in certain cases [25] . In contrast to modification of the C terminus, modifications at the peptide N terminus appear to be more widely tolerated since it has been shown that the incorporation of aromatic residues such as those found in teicoplanin [26] or positively charged residues can be tolerated [18] .…”
Section: Resultsmentioning
confidence: 99%
“…[24] However, modifying the C terminus of the linear GPA precursor peptide has been associated with a loss P450 activity, particularly with the second enzyme (OxyA) in the P450 cyclisation cascade that forms the D-O-E ring, [22] which has also been shown to be less stable than OxyB in certain cases. [25] In contrast to modification of the C terminus, modifications at the peptide N terminus appear to be more widely tolerated since it has been shown that the incorporation of aromatic residues such as those found in teicoplanin [26] or positively charged residues can be tolerated. [18] In addition to l-and d-Arg, we also explored the incorporation of l-and d-4hydroxyphenylglycine (Hpg) at position "0" of the peptide to provide substrates for the Oxy cyclisation cascade that are structurally related to newly identified examples of type V GPAs.…”
Section: Extended Peptide Design and Synthesismentioning
confidence: 99%
“…The related research had verified that the P450s enzymes performed the reactions as the scanning model depending on the experimental evidence of the continuous association/dissociation of P450s with the peptide substrates (Peschke et al 2016 ). In addition, the P450 proteins have many Tyr residues to maintain the typical heme orientation and avoid potential oxidative damage based on crystallographic experiments (Greule et al 2022 ).…”
Section: Ingenious Biosynthetic Cascades Of Gpasmentioning
confidence: 99%
“…S4–S7, ESI†) and demonstrates that the new biocatalyst is resistant to heme destruction by H 2 O 2 in the presence of a suitable substrate. 18,19…”
mentioning
confidence: 99%